IEO Annual Report 2004. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2005)
The second Annual Report of the IEO summarizes the findings and recommendations of two completed evaluation projects: on the IMF's experience with the Poverty Reduction Strategy Papers and the Poverty Reduction and Growth Facility and the role of the IMF in Argentina, 1991-2001. It also discusses the status of ongoing evaluations, and identifies potential candidates for the menu from which future IEO work programs will be chosen.